Hero on a mission : a path to a meaningful life - Miller, Donald, 1971- (HarperCollins Leadership, 2022)
Some people live stories that are filled with significance and meaning, while others feel as though they've lost the plot. In Hero on a Mission, Donald Miller explores the principles that make a story meaningful and then helps us apply those principles to our lives. The result is a life in which meaning becomes more important than productivity and our character determines our destiny. If you feel like somebody else is writing the story of your life and they aren't doing a good job, this book will help you take control of your life and edit your own story in real time --